Dampak Keluarnya NU dari Masyumi Terhadap Politik Indonesia, 1952-1960 - Martin Rizaldi; Berliana Fatihatuz Fiizha; Ervin Yunus Evendi; Muhammad 'Afwan Mufti; Shovi Wiranata Febriani (Universitas Hamzanwadi, 2023)
Nahdlatul Ulama is one of the Islamic organizations in Indonesia that prioritizes two important realities, namely Islam and Indonesia. NU played a role in the world of politics, especially in an Islamic assembly, namely MIAI (Majelis Islam A'la Indonesia) in 1937. However, the assembly was changed to Masyumi (Majelis Syuro Muslimin Indonesia) in 1943. Masyumi had a vision of becoming a political party and working together with NU, Muhammadiyah, Persis, and other Islamic organizations. The discussion will be focused specifically explain the relationship between NU and Masyumi. The aim is to explain the role of NU in Masyumi, the causes of NU's departure from Masyumi in 1952, and the political impact of NU's departure from Masyumi. The research method that will be used in this paper is historical research methods with a qualitative approach. The results of the study explained that the reason for leaving NU was getting worse because of differences in understanding between culture and ideology within Masyumi. NU's exit from Masyumi had its own political impact on Indonesia. NU which eventually became a new political party with quite good behavior in the 1955 elections, until the Masyumi organization was banned from operating in various regions and the PRRI rebellion occurred.